Мікросателітний аналіз стійких до борошнистої роси інтрогресивних ліній м’якої пшениці різного походження - Антонюк, М.З.; Штефюк, Т.В.; Терновська, Т.К. (Фактори експериментальної еволюції організмів, 2015)
Aims. Among resistant to powdery mildew wheat introgressive lines with introgressions from Ae. speltoides, Ae. sharonensis, Ae. umbellulata, identify lines with microsatellite loci allele combinations corresponding to chromosome of specifi c
homeological group of alien genome. Methods. DNA extraction using CTAB method, PCR with primers to SSR loci,
electrophoresis in PAAG, silver staining. Results. Forty introgressive lines have been screened with primers to 3, 4, 11, 5, 8,
8, 8 SSR-loci specifi c to wheat chromosomes 1D, 2D, 3D, 4D, 5D, 6D, 7D, respectively. Among identifi ed polymorphisms
we observed: spectra completely identical to one of the components of the initial cross, partly identical spectra, spectra with
new components which were not present in any of the parental forms, and null-alleles in spectra which were not characteristic
for parental spectra. Conclusions. Resistance to powdery mildew in lines derived from Aurodes is caused by the presence of
3S, 6S and 7S chromosomes or their translocations on D chromosomes in their genomes.
Keywords: introgressive wheat lines, powdery mildew resistance, Pm, microsatellite analysis, alien translocations, Aegilops
species.